Radiofrequency Ablation Compared to Surgery for the Treatment of Benign Thyroid Nodules. (22nd June 2014) - Bernardi, Stella; Dobrinja, Chiara; Fabris, Bruno; Bazzocchi, Gabriele; Sabato, Nicoletta; Ulcigrai, Veronica; Giacca, Massimo; Barro, Enrica; De Manzini, Nicolò; Stacul, Fulvio
Abstract : Objective . Benign thyroid nodules are a common occurrence whose only remedy, in case of symptoms, has always been surgery until the advent of new techniques, such as radiofrequency ablation (RFA). This study aimed at evaluating RFA efficacy, tolerability, and costs and comparing them to hemithyroidectomy for the treatment of benign thyroid nodules. Design and Methods . 37 patients who underwent RFA were retrospectively compared to 74 patients surgically treated, either in a standard inpatient or in a short-stay surgical regimen. Efficacy, tolerability, and costs were compared. The contribution of final pathology was also taken into account. Results . RFA reduced nodular volume by 70% after 12 months and it was an effective method for treating nodule-related clinical problems, but it was not as effective as surgery for the treatment of hot nodules. RFA and surgery were both safe, although RFA had less complications and pain was rare. RFA costed €1, 661.50, surgery costed €4, 556.30, and short-stay surgery costed €4, 139.40 per patient. RFA, however, did not allow for any pathologic analysis of the nodules, which, in 6 patients who had undergone surgery (8%), revealed that the nodules harboured malignant cells. Conclusions . RFA might transform our approach to benign thyroid nodules.